SARS-CoV-2 Nucleocapsid Protein is Associated With Lower Testosterone Levels: An Experimental Study - Lucio Carrasco, Caio Henrique; Noda, Paloma; Barbosa, Ana Paula; Vieira Borges da Silva, Everidiene Kinverlly; Gasque Bomfim, Camila; Ventura Fernandes, Bianca Helena; Teixeira, Thiago Afonso; Nunes Duarte Neto, Amaro; Nascimento Saldiva, Paulo Hilario; Achoa Filho, Kamal; Rodrigues Guzzo, Cristiane; Durigon, Edison Luiz; et al. (Frontiers in Physiology, 2022)
The ongoing COVID-19 pandemic represents an extra burden in the majority of public and private health systems worldwide beyond the most pessimistic expectations, driving an urgent rush to develop effective vaccines and effective medical treatments against the SARS-CoV-2 pandemic. The Nucleocapsid structural viral protein is remarkably immunogenic and hugely expressed during infection. High IgG antibodies against Nucleocapsid protein (N protein) levels were detected in the serum of COVID-19 patients, confirming its pivotal antigen role for a T lymphocyte response in a vaccine microenvironment. Currently, adverse events associated with immunizations have raised some degree of concern, irrespective of its huge benefits in dealing with disease severity and decreasing mortality and morbidity. This hitherto study evaluates histological changes in rats' testes, epididymis, prostate, and seminal vesicles and analyzes hormone levels after solely N protein inoculation. Therefore, we exposed a group of Lewis rats to weekly injections of the recombinant N protein for 28 days, while a control group was inoculated with a buffer solution. The N group revealed a more significant number of spermatozoa. Spermatozoa in the seminiferous tubules were counted in twenty 400x microscopy fields (mean of 9.2 vs. 4.6 in the control group; p < 0,01), but significantly lower testosterone levels (mean of 125.70 ng/dl vs. 309,00 ng/dl in the control group; p < 0,05) were found. No other histological and biochemical changes were displayed. Conclusively, these data suggest testicular hormonal imbalance mediated by the SARS-CoV-2 N protein that could be linked to reported post-COVID-19 syndrome hypogonadism. More relevant research might be performed to confirm this viral antigen's deleterious mechanism in the human testicular microenvironment, particular in Leydig cell function.